Neurodevelopmental Outcomes in Tetralogy of Fallot: A Systematic Review - Kalliopi Kordopati-Zilou; Theodoros Sergentanis; Panagiota Pervanidou; Danai Sofianou-Petraki; Konstantinos Panoulis; Nikolaos Vlahos; Makarios Eleftheriades (Children, 2022)
BACKGROUND: Tetralogy of Fallot (TOF) represents between 7 and 10% of the total cases of congenital heart defects (CHD) and is estimated to be the most common cyanotic CHD, requiring medical or surgical intervention within the first year of life. Current advances in prenatal screening and fetal echocardiography led to increased rates of prenatal diagnosis of TOF. Furthermore, improvements in initial medical care, surgical repair, and long-term care are associated with excellent long-term survival until adulthood. Consequently, issues of morbidity have come under the spotlight, specifically neurodevelopmental and psychiatric adverse outcomes, which affect the quality of life of TOF survivors. METHOD: This study is a systematic review of English articles, using PUBMED and applying the following search terms, Tetralogy of Fallot, neurodevelopment, autism, cerebral palsy, attention-deficit hyperactivity disorder. Data were extracted by two authors. RESULTS: Most researchers suggest that TOF survivors score lower in neurodevelopmental tests than healthy populations of the same age and are in danger of neurodevelopmental impairments. Furthermore, it is suggested that TOF adolescents show higher rates of psychiatric disorders. CONCLUSIONS: The neurodevelopment of TOF survivors is not intensively studied. Existing studies in TOF survivors focus on different developmental aspects, using different evaluation methods and thus making conclusions for either one of the four aspects of neurodevelopment (executive function, cognition, and adaptive function, speech-language and motor function, or neuropsychiatric domain). The poor outcomes of these isolated studies indicate the need for future research as well as for continuous neuropsychological assessment and close monitoring of children and adolescents with TOF.